Radiation Effects on Embedded Systems - Velazco, Raoul; Fouillat, Pascal; Reis, Ricardo (Springer Netherlands : Imprint: Springer, 2007)
Radiation Effects on Embedded Systems aims at providing the reader with the major guidelines for coping with radiation effects on components supposed to be included in today's applications devoted to operate in space, but also in the atmosphere at high altitude or at ground level. It contains a set of chapters based on the tutorials presented at the International School on Effects of Radiation on Embedded Systems for Space Applications (SERESSA) that was held in Manaus, Brazil, from 20 to 25 November 2005. This book will provide all IC engineers with useful information regarding outside (environmental) influences on their designs and is an excellent reference.